Convivencia familiar y su repercusión en la estabilidad afectiva durante la crisis del covid 19, en la ciudad de Quevedo - Los Ríos - Aviles Mora, Katiuska Thalya (2021)
Family coexistence has repercussions in affective stability in the face of the COVID-19 crisis, taking into account how essential it is to know the family system in which people develop, their interaction and your perception of ideas. How it performs its functions, roles, the approach to limits, hierarchies in the family, within them, knowing which ones are more prone to affective changes, in which feeling good about oneself develops, and therefore with the other members of the family. Taking into account the crisis that is taking place in these times, going through the confinement of all families, causing them to interact more time with each other, reflecting distortions in their affective behaviors, in their decision-making, in the way of expressing their ideas or criteria. Strengthening their favorable affective development, psychoeducation to the family system, which will promote significant changes in a before and after family life.